Erratum - Editorial (Vojnosanitetski Pregled)
In the Editorial 1 published in the first (January) issue, 2017, of the Vojnosanitetski pregled, there was an error in the surname of one of the reviewers. In the Table 2 in which names of reviewers of the Journal in 2016 were given, on the page 7, 4th column right, the name of a reviewer Vanović Mirjana should have read as Životić-Vanović Mirjana. Link to the corrected article 10.2298/VSP1701005D